2013
DOI: 10.1155/2013/854572
|View full text |Cite
|
Sign up to set email alerts
|

Role of Candidate Genes Regulating Uterine Prostaglandins Biosynthesis for Maternal Recognition of Pregnancy in Domestic Animals

Abstract: The survivability and opportunity of successful development of an embryo are influenced directly or indirectly by factors controlling uterine microenvironment. Out of all factors, hormones such as prostaglandins (PGs) released during the preimplantation period influence molecular interactions involved in maintenance of pregnancy through reciprocal interactions between the conceptus and endometrium. PGs are important regulators of female reproductive functions, namely, ovulation, uterine receptivity, implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Prostaglandins are well known for their importance in female reproduction [68] including implantation, ovulation and uterine maintenance [36,40]. In uterine tissue prostaglandins work through different receptors and its function depends on expression of receptors [13].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins are well known for their importance in female reproduction [68] including implantation, ovulation and uterine maintenance [36,40]. In uterine tissue prostaglandins work through different receptors and its function depends on expression of receptors [13].…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm the results from our earlier study of plasma PL of cats fed these same three diets during a 56-d period ( 8 ) and extend them to include fatty acid compositions of feline reproductive tissues and evidence for active Δ5-desaturation in uterine tissue. The uterine accretion of ARA with the GL diet would be expected to provide the substrate for PG synthesis in support of the successful full-term pregnancy ( 10 ) . Thus, a diet containing GLA from vegetable sources may be possible to meet feline ARA requirements for reproduction in the absence of a pre-formed animal-based ARA source.…”
Section: Discussionmentioning
confidence: 99%
“…PGF 2α is the main active PGs in mediating myometrial contraction related to the onset of labor in sheep (LIGGINS, G., C., GRIEVES, & SUSAN, 1971). PGFS is a monomeric enzyme that catalyzes the conversion of PGH2 to PGF 2α (Rohit et al, 2013). It has been demonstrated that both uterine and placental tissues express PGFS (Palliser & H., 2004;Xiao, 1999).…”
Section: Genomic Selection Footprint Regions Related To Domesticationmentioning
confidence: 99%